Eating in a colonial hospital: Notes on the diets in three hospitals of New Granada in the late 18th century (2012)
This paper studies some aspects of the diet of three hospitals of the New Granada in the late 18th century. To do this, we analyze accounting records found in the General National Hall of Records which recorded the purchase of foodstuffs in three San Juan de Dios hospitals located in Santafé de Bogotá, Cartagena, and Portobelo (Panama). The ingredients and recipes recorded describe a specific moment in the history of the diet in the hospital, determined by the religious and tributary model of the monastic and conventual world. The foods eaten then were influenced by the economic, cultural, religious, and hygienic circumstances surrounding them.